2005
DOI: 10.1073/pnas.0503324102
|View full text |Cite
|
Sign up to set email alerts
|

Reversal of amyloid-induced heart disease in desmin-related cardiomyopathy

Abstract: Amyloid oligomers, similar to the toxic entities found in Alzheimer's disease patients and in other amyloid-based diseases, are present in cardiomyocytes derived from human heart-failure patients and in animal models of desmin-related cardiomyopathy (DRM). The R120G mutation in ␣-B-crystallin (CryAB) causes DRM and is characterized by aggresomes containing CryAB R120G and amyloid oligomer. In this study, we show that aggresome levels do not correlate with disease. Blocking aggresome formation results in increa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

11
128
0
7

Year Published

2006
2006
2020
2020

Publication Types

Select...
4
4

Relationship

1
7

Authors

Journals

citations
Cited by 102 publications
(146 citation statements)
references
References 39 publications
11
128
0
7
Order By: Relevance
“…Earlier studies of DRC animal models showed that the desmin aggregates and sarcomere disarray accompany and are partially responsible for impairment of cardiomyocyte contractility,58, 59 but these ultrastructural changes do not lead to cardiomyocyte cell death by themselves 58. Our data support the hypothesis that aberrant mitochondrial fission is likely involved in mitochondrial dysfunction and the apoptotic cell death associated with desminopathy.…”
Section: Discussionsupporting
confidence: 85%
“…Earlier studies of DRC animal models showed that the desmin aggregates and sarcomere disarray accompany and are partially responsible for impairment of cardiomyocyte contractility,58, 59 but these ultrastructural changes do not lead to cardiomyocyte cell death by themselves 58. Our data support the hypothesis that aberrant mitochondrial fission is likely involved in mitochondrial dysfunction and the apoptotic cell death associated with desminopathy.…”
Section: Discussionsupporting
confidence: 85%
“…Our studies of cultured human muscle fibers bearing the transthyretin Val122Ile mutation and overexpressing AβPP indicated that increased muscle fiber degeneration is associated with increased Aβ oligomerization [11]. Of interest is a recent study related to cultured cardiomyocytes which experimentally expressed both αBC bearing the R120G mutation, causing desmin-related myopathy [30], and a toxic amyloidogenic peptide PQ81 [31]. Those cardiomyocytes had pronounced aggresome formation but, interestingly, inhibition of the aggresome formation through additional expression of the wild αBC led to increased accumulation of PQ81 amyloidoligomers and increased cellular toxicity [31].…”
Section: Discussionmentioning
confidence: 98%
“…Of interest is a recent study related to cultured cardiomyocytes which experimentally expressed both αBC bearing the R120G mutation, causing desmin-related myopathy [30], and a toxic amyloidogenic peptide PQ81 [31]. Those cardiomyocytes had pronounced aggresome formation but, interestingly, inhibition of the aggresome formation through additional expression of the wild αBC led to increased accumulation of PQ81 amyloidoligomers and increased cellular toxicity [31]. That study suggests that, while a mutated αBC causes aggregation of a toxic amyloidogenic protein, prevention of aggresome formation by maintaining amyloidogenic protein in the form of oligomers was associated with increased toxicity [31].…”
Section: Discussionmentioning
confidence: 99%
“…12,90 Aggregation of amyloid-like material was recently demonstrated to be a typical feature of many human cardiomyopathies, especially those caused by mutations in CRYAB. 91 Physiologically, the inclusion of misfolded proteins into aggregates was proposed to be a protective mechanism in alphaB-crystallinopathy, 92 linking desminopathy to a broad class of conformational neurodegenerative diseases. Remarkably, desmin knock-out and transgenic mice show less severe pathology as compared to the CRYAB transgenic mice.…”
Section: Role Of Alphab-crystallinmentioning
confidence: 99%